Spatial patterns of prostate-specific antigen testing in asymptomatic men across Australia: a population-based cohort study, 2017–2018. (April 2023) - Kohar, A.; Cramb, S.M.; Pickles, K.; Smith, D.P.; Baade, P.D.
Abstract: Objectives: In Australia, while prostate-specific antigen (PSA) testing rates vary by broad area-based categories of remoteness and socio-economic status, little is known about the extent of variation within them. This study aims to describe the small-area variation in PSA testing across Australia. Study design: This was a retrospective population-based cohort study. Methods: We received data for PSA testing from the Australian Medicare Benefits Schedule. The cohort included men ( n  = 925, 079) aged 50–79 years who had at least one PSA test during 2017–2018. A probability-based concordance was applied across multiple iterations ( n  = 50) to map each postcode to small areas (Statistical Areas 2; n  = 2, 129). For each iteration, a Bayesian spatial Leroux model was used to generate smoothed indirectly standardized incidence ratios across each small area, with estimates combined using model averaging. Results: About a quarter (26%) of the male population aged 50–79 years had a PSA test during 2017–2018. Testing rates among small areas varied 20-fold. Rates were higher (exceedance probability>0.8) compared with the Australian average in the majority of small areas in southern Victoria and South Australia, south-west Queensland, and some coastal regions of Western Australia but lower (exceedance probability<0.2) in Tasmania and Northern Territory. Conclusions: The substantial geographical variation in PSA testing rates across small areas of Australia may be influenced by differences in access to and guidance provided by clinicians and attitudes and preferences of men. Greater understanding of PSA testing patterns by subregions and how these patterns relate to health outcomes could inform evidence-based approaches to identifying and managing prostate cancer risk.